2020
DOI: 10.1186/s12935-020-01210-1
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of microRNA-135b inhibits invasion, migration, and stemness of CD24+CD44+ pancreatic cancer stem cells through JADE-1-dependent AKT/mTOR pathway

Abstract: Background: Recent studies have emphasized determining the ability of microRNAs (miRNAs) as crucial regulators in the occurrence and development of pancreatic cancer (PC), which continues to be one of the deadliest malignancies with few effective therapies. The study aimed to investigate the functional role of miR-135b and its associated mechanism to unravel the biological characteristics of tumor growth in pancreatic cancer stem cells (PCSCs). Methods: Microarray analyses were initially performed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Zhou J et al demonstrated miR-135b also had higher expression in pancreatic cancer stem cells and tissues. Silencing miR-135b-5p suppressed stemness of pancreatic cancer stem cells by targeting JADE-1 (40). MiRTarBase (23), TargetScan (24), and DIANA-microT (25) predicted the complementary gene of miR-135b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou J et al demonstrated miR-135b also had higher expression in pancreatic cancer stem cells and tissues. Silencing miR-135b-5p suppressed stemness of pancreatic cancer stem cells by targeting JADE-1 (40). MiRTarBase (23), TargetScan (24), and DIANA-microT (25) predicted the complementary gene of miR-135b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the miR-135b cluster, which lead to its transcriptional activation, was likely due to amplifying its sequence. At present, upregulated miR-135b has been reported in a variety of cancers, and it has been shown to drive multiple malignant phenotypes [28][29][30]. The amplification of miR-135b in colorectal cancer cells enhanced the chemotherapy resistance for doxorubicin, oxaliplatin, and 5-FU [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Transfection with anti-miR-221 was also found to reduce tumor growth in a PDX model of CRC in vivo [49]. Meanwhile, in pancreatic cancer, treatment with anti-miR-135b suppressed tumor growth in vivo [76]. Similarly, treatment with anti-miR-181 decreased the population of EpCAM + HCC stem cells in vivo [108].…”
Section: The Role Of Mirnas In Developing Therapeutics Targeting Gi Cscsmentioning
confidence: 91%
“…Similarly, the expression of miR-135b was found to be upregulated in CD44 + /CD24 + /EpCAM + CSCs. Inhibiting miR-135b with an antisense oligonucleotide, anti-miR-135b, decreased the expression of stemness markers such as NANOG, ALDH1, SOX2, and OCT-4 [76].…”
Section: The Role Of Mirnas In Pancreatic Cancer Stem Cellsmentioning
confidence: 99%